1994
DOI: 10.1063/1.112772
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of silicon nitride prepared by plasma-enhanced chemical vapor deposition at low temperature

Abstract: Hydrogenated amorphous silicon nitride (a-SiNx:H) films have been fabricated by plasma-enhanced chemical vapor deposition at temperatures ranging from 50 to 250 °C. It is found that as soon as the samples are taken out from the reaction chamber and exposed to the atmosphere, the a-SiNx:H films start to oxide. The oxidation processes are monitored using infrared absorption spectroscopy. A model of porous ‘‘fractal-like network’’ structure, which is probably inherent in low-temperature deposition, is proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 10 publications
2
53
0
Order By: Relevance
“…For a-SiN deposited at low substrate temperatures (Ϸ100°C), Liao et al observed rapid oxidation to hydrated SiO 2 in humid air at a rate of 800 nm/day, while films deposited at 225°C oxidized at Ϸ1.3 nm/day. 26 IR spectral data indicated that the SiONOSi and -SiONH bonds were oxidized to SiOOOSi and SiOOH. Amorphous SiC films produced by PECVD at low temperatures (200 -400°C), however, are stable and tolerate wet processing in aggressive acidic and alkaline etchants.…”
Section: Discussionmentioning
confidence: 99%
“…For a-SiN deposited at low substrate temperatures (Ϸ100°C), Liao et al observed rapid oxidation to hydrated SiO 2 in humid air at a rate of 800 nm/day, while films deposited at 225°C oxidized at Ϸ1.3 nm/day. 26 IR spectral data indicated that the SiONOSi and -SiONH bonds were oxidized to SiOOOSi and SiOOH. Amorphous SiC films produced by PECVD at low temperatures (200 -400°C), however, are stable and tolerate wet processing in aggressive acidic and alkaline etchants.…”
Section: Discussionmentioning
confidence: 99%
“…Postdeposition oxidation has been also reported for rf PECVD a-SiN x :H films deposited at low temperature. 33 It should be mentioned that the given concentrations are taken from the bulk region of the ERD depth profiles. The ETP NH 3 films as shown in Fig.…”
Section: Etp Deposited A-sin X :H Films From N 2 -Sih 4 and Nh 3 -Sihmentioning
confidence: 99%
“…1 -8 A large amount of basic and applicative studies have been performed using different spectroscopic techniques. In particular, Lin and Lee 9 and Liao et al 10,11 used infrared spectroscopy to follow the oxidative kinetics over long time scales. They demonstrated that samples produced by lowtemperature PECVD are porous in the bulk structure and, in particular, at the surface level.…”
Section: Introductionmentioning
confidence: 99%